Sexual maturity of the speckled swimming crab Arenaeus cribrarius (Lamarck, 1818) (Decapoda, Brachyura, Portunidae), in the Ubatuba Littoral, São Paulo state, Brazil - Pinheiro, MAA; Fransozo, A. (Brill Academic Publishers, 1998)
The sizes at morphological and physiological maturity of male and female Arenaeus cribrarius were estimated to determine if both events are synchronous. Animals were captured with otto-trawls at Ubatuba, Brazil. A total of 2356 specimens, 977 males and 1379 females, were obtained. The major carapace width without spines (CW), the propodus length of the major cheliped (PL) and the width of the 5th abdominal somite (AW) were measured with vernier calipers. Allometric relationships and gonadal development were analyzed to determine the maturity in both sexes. The size at the onset of male morphological maturity was estimated at CW 52 mm, smaller than the CW 63.4 mm physiological maturity size observed. For females, these events are synchronous since both estimates converged at CW 59.7 mm. The onset of functional sexual maturity in A. cribrarius at CW 63.4 and 59.7 mm in males and females, respectively, would indicate a minimum size of CW 64 mm for fishing purposes. Differences between allometric and gonadal estimates indicate the importance of considering both methods. A comparison of the present results with other available data in portunid crabs is provided.